Access to post-exposure prophylaxis following sexual exposure for men who have sex with men in an Irish healthcare setting. (July 2015) - McFaul, K; Rowley, D; O'Reilly, A; Clarke, S
Men who have sex with men experience disproportionate rates of HIV acquisition. Post-exposure prophylaxis following unprotected sexual exposure reduces HIV transmission. Our aim was to assess access to post-exposure prophylaxis for men who have sex with men in Irish emergency departments. We contacted all national 24-hour adult emergency departments describing two scenarios; a seronegative man who has sex with men receiving unprotected insertive anal intercourse from a seropositive partner and secondly a woman sustaining a needle-stick injury from an unknown source. We recorded and compared responses regarding post-exposure prophylaxis advice in each situation. High proportions of emergency departments offered post-exposure prophylaxis for both situations despite minimal evidence to support use in needle-stick injury. Men who have sex with men were less likely to be asked to attend emergency departments for post-exposure prophylaxis administration than a person experiencing needle-stick injury. Men who have sex with men were less likely to be offered baseline serological testing for blood borne infections. Men who have sex with men were as likely as needle-stick injury to receive advice from healthcare workers in emergency departments and consultation durations were similar. This study identifies a need to educate healthcare workers in emergency departments on appropriate use of post-exposure prophylaxis following sexual exposure for men who have sex with men. Health care workers must appreciate the importance of post-exposure prophylaxis presentations as opportunities for intervention and HIV screening.